Penerapan Teknologi Penggunaan Beton Porous Precast untuk Perkerasan Jalan Pejalan Kaki di Kelurahan Ngadirgo Kecamatan Mijen Kota Semarang - Jamal Mahbub; Setiaji Pamungkas, Nur; Mulyo Wicaksono, Teguh; Wahjoedi, Wahjoedi; Wasino, Wasino; Suwarto, Suwarto; Risman, Risman; Junaidi, Junaidi; Suparman, Suparman; Suroso, Suroso; Puji Lestari, Nor; Yahya S.B., Lalu; Rio Devilito (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Scientific knowledge in the field of road pavement in the Civil Construction Study Program, among others, studies pavement materials, permeability, soil mechanics, and types of pavement. The road pavement itself is divided into several types, namely rigid pavement and flexible pavement. Government policy related to the arrangement of the city of Semarang regarding catchment areas as rainwater catchment areas are the hilly areas of Mijen and Mount Pati. The rigid pavement model with concrete and bending using asphalt will cover the surface of the ground so that rainwater will immediately flow and be wasted without going through the infiltration process. With the concrete shaft pavement method, it is hoped that it will be able to produce pavement for pedestrians that conform to applicable load standards but still has a role as an infiltration area. In accordance with the special specification regulations for porous concrete skh 1514 of the Director General of Highways requires that porous concrete is concrete that has a minimum cavity of 20% of the volume of concrete. The application of the use of porous concrete for road pavement is expected to be able to provide insight and knowledge to the community regarding the importance of regional development without reducing the role of infiltration areas. The installation of this porous concrete serves as a walkway for pedestrians in Ngadirgo Village which is environmentally friendly because it does not give a waterlogging effect, but the existing water can directly seep through the cavities in the concrete construction.